Child saliva microbiota and caries: - Muhoozi, K. M. Grace; Li, Kelvin; Atukunda, Prudence; Skaare, B. Anne; Willumsen, Tiril; Enersen, Morten; Westerberg, C. Ane; Morris, Alison; Vieira, R. Alexandre; Iversen, O. Per; Methé, A. Barbara (Scientifc Reports, 2022)
Undernutrition is a public health challenge in sub-Saharan countries, including Uganda. In a previous randomized controlled trial (RCT) with a nutrition, hygiene and stimulation education intervention among mothers of 6 months’ old children, we found less caries in the intervention group when the children were 36 months of age. We now examined the efects of (i) the intervention on the microbiota, (ii) microbiota on caries, and (iii) the intervention and microbiota on caries. The original RCT comprised 511 mother/child pairs whereas in the current study we had access to data from 344/511 (67%) children aged 36 months. The saliva microbiota was determined using 16S rRNA gene sequencing. Carious lesions (a proxy for dental health) were identifed using close-up intra-oral photographs of the upper front teeth. Statistical models were used to determine hostmicrobiota associations. The intervention had a signifcant efect on the microbiota, e.g. an increase in Streptococcus abundance and decreases in Alloprevotella and Tannerella. Signifcant associations between the microbiota and dental caries were identifed: Positive associations of Capnocytophaga and Tannerella suggest that these taxa may be deleterious to dental health while negative associations of Granulicatella, Fusobacterium, and Abiotrophia suggest taxa potentially benefcial or benign contributors to dental health. Based on taxonomic profles, the efects of the intervention and microbiota on dental health may be independent of one another. Educational interventions with emphasis on nutrition and oral hygiene may provide a feasible strategy to decrease progression of childhood caries in low-resource settings.
a randomized controlled maternal education trial in rural Uganda
Article